Explaining the relationships between self-learning capacity and academic success in EMI from a self-image perspective. - Bali, Sandrotua; Chiu, Thomas K. F.; Chen, Tsai-Tsing; Liu, Ming-Chou; Lin, Cheng-Yi (Journal of Multilingual & Multicultural Development, 2026)
The massive trend of English as a Medium of Instruction (EMI) courses in non-Anglophone coutries is rapidly growing. Therefore, this study aims to examine the factors influencing students' academic success in EMI settings. Data collected from 826 university students enrolled in EMI courses across science, engineering, and social programmes were analysed using Structural Equation Modelling (SEM). The findings revealed that perceived learning capacity, encompassing self-regulation and self-efficacy, significantly impacts students' perceived success in EMI courses. This research offers a novel perspective on the dynamics of EMI, highlighting the importance of perceived self-learning capacity and L2 learner self-images. Our findings offer valuable insights for educational institutions, universities, and students, informing efforts to enhance EMI programmes and boost student outcomes.